Anti-tissue factor (TF9-10H10) treatment reduces tumor cell invasiveness in a novel migratory glioma model - Harter, Patrick Nikolaus; Capper, David (Neuropathology, 2013)
In vitro and descriptive studies of human tissue samples revealed the pro-coagulant glycoprotein tissue factor (TF) as a potent player in glioma cell infiltration that is activated by hypoxia and has also been shown to be upregulated by mutations of TP53 or PTEN. Here we present the morphological and genetic characterization of a novel glioblastoma in vivo model and provide evidence that treatment with an antibody targeting TF leads to reduced glioma cell invasiveness. Therefore, we established a murine xenograft treatment model by transplanting the angiogenic and diffusely infiltrating human glioma cell line MZ-18 with endogenous TF expression into nude mice brains and treating these mice with an intracranial osmotic pump system continuously infusing a monoclonal antibody against TF (mAb TF9-10H10). The human MZ-18 cell line harbors two TP53 mutations resulting in a strong nuclear accumulation of p53, thereby facilitating the unambiguous identification of tumor cells in the xenograft model. Intracranial application of TF9-10H10 significantly reduced invasion of MZ-18 cells compared to mock-treated control animals. The extent of activated blood vessels was also reduced upon anti-TF treatment. Thus, targeting the TF pathway might be a promising treatment strategy for future glioblastoma therapies, by affecting both invading tumor cells and tumor vasculature.
Gesehen am 26.02.2021